Analisis Pengaruh Tekanan Angin Ban Terhadap Jarak Pengereman Sepeda Motor Honda Supra X 125 CC - Bhahak Fendi Baihaqi, Setyo; Fitri Naryanto, Rizqi (Pusat Penelitian dan Pengabdian Masyarakat (P3M), 2025)
Tires are a vital component of a motor vehicle that serves to minimize vibrations caused by uneven road surfaces, stabilizing the vehicle on the road and facilitating the driver's control over the vehicle's direction. Tire pressure that does not meet standard specifications will affect the braking performance, making it suboptimal, which can result in less effective vehicle braking. This research will discuss the influence of varying wind pressure in tyres on the effective braking distance of Honda Supra X 125 cc motorcycles to prevent accidents caused by tyre blowouts. In this test, the author will compare three (3) variations of tire pressure at the front tire position, namely 20, 29, and 40 Psi. The initial speed of the vehicle in this test is 40 km per hour and 60 km per hour, until the vehicle comes to a stop. This test is limited to dry road surface conditions and the rear tire pressure is kept the same at 33 Psi. From the results of the test, we can conclude that the best (shortest) braking distance at initial speeds of 40 km per hour and 60 km per hour is still better at a tire pressure variation of 29 Psi (in accordance with the guidelines of the manual book or the standards of Honda motorcycle manufacturers).